Hospitality employee management and supervision : concepts and practical applications - Sommerville, Kerry L. (Hoboken, New Jersey : John Wiley & Son, Inc., 2007)
n many hospitality establishments, one manager or supervisor is the entire human resources department, making all the hiring and training decisions, often without having a formal human resources background. Filling this knowledge gap, [this book] provides both busy professionals and students with a one-stop comprehensive guide to human resources in the hospitality industry. Rather than taking a theoretical approach, this text provides a hands-on, practical, and applications-based approach. The coverage is divided into four sections: legal considerations, employee selection, employee orientation and training, and communication and motivation.
Legal landscape: Introduction to hiring and supervising employees; Hospitality manager's legal challenges; Wage and hour laws affecting salaried, hourly, and tipped employees; Common law, negligent hiring, and employee rights; Working with unions -- Employee selection process: Job descriptions and job specifications; Employee handbook; Advertising and recruiting; Applications, interviews, and background checks -- Orientation and training: New-employee orientation; Training to performance standards -- Communication and motivation: Performance appraisals that work; Effective communication and feedback; Employee discipline; Employee motivation through quality leadership.
Includes bibliographical references and index.
Keywords: HOSPITALITY INDUSTRY -- PERSONNEL MANAGEMENT